O discurso sobre o Nordeste no livro didático de língua portuguesa: nos fios da memória, a construção de uma identidade regional - Silva , Vanessa Alves da (2018)
The concept of region is not specifically linked to territory or to a political or economical cutting. Surpassing geographical limits, a region also represents an imagistic discursive construction, a product of several ways of saying. In this context, a series of positive and negative discourses legitimated by social using created the Northeast Region and their inhabitants, the “Nordestinos”. Therefore, taking as a theoretical input the perception of Albuquerque Júnior (2011) and the French branch of Discourse Analysis (DA), fundamentally the concepts of Michel Pêcheux (1997, 1999, 2008, 2009), as well as the studies of contemporary researchers like Eni Orlandi (1998, 2001, 2007, 2010, 2012) and Freda Indrusky (2005 e 2008), this paper aims to make considerations on the discourse presented in textbooks about Brazilian Northeast Region written in Portuguese. Considering textbooks besides being a powerful instrument of ideological transmission are a valuable tool in pedagogical praxis, this study tried to identify points about the discursive subject and their memories brought up from narratives and literary texts present in school compendiums about this region and its inhabitants written in their mother-tongue. In this context, the present research tries to make it clear memory is part of the conditions in which the discourse is produced, along with the subject and the situation. However, the memory studied by DA is not the cognitive one but the social one, that is to say, discourses created from sociohistorical elements which are taken again, repeated and made regular. As a bibliographic study, the present research’s corpus are the book collections in mother tongue Projeto Radix: “Raiz do conhecimento”, by Ernani Terra e Floriana Toscano Cavallete, and “Para Viver juntos” (9th year), with Andressa Munique de Paiva as the chief editor. These compendiums were used in public and private teaching institutions in Recife and its metropolitan region, from 2012 to 2016. Results show that even though official documents have an attentive look on representing cultural diversity, textbooks in Portuguese language still present several discourses that stereotype the region and its inhabitants. Therefore, some discourses go around the society and produce a symbolic net which shape identities. Namely, by repeating and regularizing what is told, identity devices are created and brought up from memory nets. This is what happen to the identity of territory and people from Brazilian Northeast Region, notoriously imagistic-discursive constructions, as it will be seen at the presentations shown in this dissertation.